(untitled) (Proceedings of the International Conference on Public Health, 2021)
The earthquake can cause a potential transmission of the disease after the disaster. One of the infectious diseases that could potentially be a post-earthquake outbreak is Dengue Hemorrhagic Fever (DHF). The earthquake, followed by a tsunami and liquefaction that struck Palu’s city, Sigi’s regency, and the regency of Donggala in Central Sulawesi in September 2018, led to the increased transmission of the dengue hemorrhagic fever disease in all three regions. This research aims to determine the incidence rate of DHF in the affected areas of the earthquake disaster in Central Sulawesi. The data used involved the number of DHF cases before and after the earthquake (2015- 2019) in Palu, Sigi, and Donggala. The data was obtained from the Health Office of Central Sulawesi Province. The results of the analysis showed that the Incidence Rate (IR) of DHF in 2019 was 165.94 (Palu), 77.13 (Sigi), and 62.86 (Donggala). Dengue Hemorrhagic Fever’s IR increased after the earthquake in Palu, Sigi, and Donggala in 2019 that marked the outbreak of DHF in all three regions. The highest increase in the DHF cases was found in Palu. The efforts to improve the health system are needed by strengthening DHF diagnosis, DHF case reporting, vector surveillance, active temephos distribution, and community empowerment to reduce DHF vector breeding sites.